ÐÑƒÐºÐ»ÐµÐ¸Ñ€ÑƒÑŽÑ‰Ð¸Ðµ Ð°Ð³ÐµÐ½Ñ‚Ñ‹ Ð³Ñ€Ð¸Ð±Ð¾Ð² Ð¸ Ñ€Ð°ÑÑ‚ÐµÐ½Ð¸Ð¹ - Gulevskiy, A. K.; Relina, L. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
The modern ideas of fungus and plant nucleating agents’ structure and activity are presented in the review. The data on nucleators in representatives of the Kingdoms Plants and Fungi are compared with those on nucleators of bacterial origin.